Extremely Rapid Self‐Healable and Recyclable Supramolecular Materials through Planetary Ball Milling and Host–Guest Interactions. Issue 39 (26th August 2020) - Park, Junsu; Murayama, Shunsuke; Osaki, Motofumi; Yamaguchi, Hiroyasu; Harada, Akira; Matsuba, Go; Takashima, Yoshinori
Abstract: The host–guest interaction as noncovalent bonds can make polymeric materials tough and flexible based on the reversibility property, which is a promising approach to extend the lifetime of polymeric materials. Supramolecular materials with cyclodextrin and adamantane are prepared by mixing host polymers and guest polymers by planetary ball milling. The toughness of the supramolecular materials prepared by ball milling is approximately 2 to 5 times higher than that of supramolecular materials prepared by casting, which is the conventional method. The materials maintain their mechanical properties during repeated ball milling treatments. They are also applicable as self‐healable bulk materials and coatings, and they retain the transparency of the substrate. Moreover, fractured pieces of the materials can be re‐adhered within 10 min. Dynamic mechanical analysis, thermal property measurements, small‐angle X‐ray scattering, and microscopy observations reveal these behaviors in detail. Scars formed on the coating disappear within a few seconds at 60 °C. At the same time, the coating shows scratch resistance due to its good mechanical properties. The ball milling method mixes the host polymer and guest polymer at the nano level to achieve the self‐healing and recycling properties. Abstract : Planetary ball milling increases the mobility of polymer chains. The increased mobility helps supramolecule‐like properties to be achieved, as these properties do not appear with low chain mobility. These supramolecular materials have tough mechanical properties, rapid self‐healing properties, and recyclable properties.